GENETIC ARCHITECTURE OF QUALITY TRAITS IN BELL PEPPER - VIBHUTI SHARMA; SONIA SOOD (The Bioscan, 2024)
Fourty six bell pepper genotypes were evaluated for quality traits during the summer-rainy season 2015. The estimates of PCV and GCV were high for capsanthin (45.84%, 45.70%) and ascorbic acid (40.06% and 40.02%); moderate for marketable fruit yield per plant (29.57%, 28.65%) and TSS (22.81%, 21.37%). High to moderate heritability along with high to moderate genetic advance were observed for marketable fruit yield per plant (93.84%, 57.16%), capsanthin ( 99.39%, 93.86%), ascorbic acid ( 99.83%, 82.37%) and TSS ( 87.76%, 41.23%), indicated additive genetic control for the inheritance of these traits and could be improved through selection. Low heritability with low genetic advance for pericarp thickness (22.22%, 6.28%) indicating non additive gene action. Genotypic correlations were higher than their corresponding phenotypic ones indicating strong inherent association among such traits, the phenotypic expression of correlation gets reduced under the influence of environment. The genotypic correlations were partitioned into direct and indirect effects to know the relative importance of the components. Ascorbic acid content (-0.105, -0.108) and TSS (-0.153, -0.175) had negative correlation with marketable fruit yield per plant. Direct negative effect on fruit yield per plant was found with ascorbic acid, capsanthin and TSS. Therefore, indirect selection practiced on these traits will result in the improvement of respective characters and fruit yield.